Fertility preservation for women with breast cancer before chemotherapy: a systematic review and meta-analysis. Issue 2 (February 2022) - Chen, Chih-Ning; Chang, Lu-Te; Chen, Chi-Huang; Tam, Ka-Wai
Abstract: The preservation of fertility in women of childbearing age with breast cancer is challenging because the time for ovarian stimulation is restricted and only a limited number of oocytes can be retrieved before gonadotoxic therapies. The aim of this meta-analysis was to evaluate the fertility preservation outcomes after ovarian stimulation with various protocols in women with breast cancer. PubMed, Embase and the Cochrane Library were searched. Twenty-two studies comparing the outcomes of women with breast cancer receiving random-start ovarian stimulation or conventional protocol; single or double ovarian stimulation cycles; and coadministration of aromatase inhibitors or tamoxifen were included. Random-start ovarian stimulation resulted in a comparable number of retrieved oocytes to the conventional protocol. Two ovarian stimulation cycles had significantly higher numbers of total retrieved oocytes than one cycle (mean difference 7.91, 95% confidence interval [CI] 3.42 to 12.40). Coadministration of letrozole and tamoxifen showed similar results for retrieved oocytes to those without. A significantly lower peak serum oestradiol concentration was observed in letrozole-based groups than in letrozole-free groups (mean difference −1.22; 95% CI −1.42 to −1.02). In conclusion, this study indicated that implementing random-start protocols to shorten the duration of waiting for ovarian stimulation, applying two ovarian stimulation cycles, and coadministration of letrozole can lead to more desirable outcomes.